ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL URAIAN ALJABAR - Fadya, Saira Inka; Ardiyanti, Yusi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research aims to analyze students' critical thinking abilities in solving algebraic essay questions based on Ennis' critical thinking ability indicators. This study uses a qualitative method. The subjects in the research were 36 class VII D students at one of the Karawang Middle Schools. Sampling used saturated sampling. Data collection through 2 questions describing algebra material with validated instruments. Subjects were divided into 5 groups, namely very good, good, fair, poor, and not good level students. The research results showed that 30 students were in the very good category and were able to solve 2 questions correctly. In the good category, 4 students were able to solve 2 questions but were not thorough enough. In the sufficient category, 2 students can answer 1 question correctly. There are no students in the poor or bad categories. The average student score was 93. It was concluded that the student’s critical thinking skills in algebra material with 36 students at one of the Karawang Middle Schools were classified as having very good critical thinking skills.